2022
DOI: 10.3389/fnmol.2022.859166
|View full text |Cite
|
Sign up to set email alerts
|

Protein Tyrosine Phosphatase Receptor Type D Regulates Neuropathic Pain After Nerve Injury via the STING-IFN-I Pathway

Abstract: Neuropathic pain is usually caused by injury or dysfunction of the somatosensory system, and medicine is a common way of treatment. Currently, there are still no satisfactory drugs, like opioids and lidocaine, which carry a high risk of addiction. Protein tyrosine phosphatase receptor type D (PTPRD) is a known therapeutic target in addiction pathways and small molecule inhibitors targeting it, such as 7-butoxy illudalic acid analog (7-BIA), have recently been developed to tackle addition. PTPRD is also upregul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 43 publications
0
10
0
1
Order By: Relevance
“…In addition, STING regulates the type 1 interferon signaling in dorsal root ganglion sensory neurons, which has been disclosed to control nociception in bone cancer pain models (Donnelly et al, 2021 ). Consistently, in chronic constriction injury-induced neuropathic pain, protein tyrosine phosphatase receptor type D (PTPRD) activates STING-type 1 interferon pathway in dorsal root ganglion and displays an analgesic effect (Sun et al, 2022 ). In the light of this, researchers have reviewed that IFN-α and IFN-β may rapidly suppress neuronal activity and synaptic transmission to potent analgesia via nongenomic regulation (Tan et al, 2021 ), while the discrepancy in antinociceptive against pronociceptive effects of type 1 interferons may ascribe to various conditions, and the exact role of STING/type 1 interferons in chronic pain requires further investigation.…”
Section: The Main Downstream Signaling Pathways Of Cgas-sting In Chro...mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, STING regulates the type 1 interferon signaling in dorsal root ganglion sensory neurons, which has been disclosed to control nociception in bone cancer pain models (Donnelly et al, 2021 ). Consistently, in chronic constriction injury-induced neuropathic pain, protein tyrosine phosphatase receptor type D (PTPRD) activates STING-type 1 interferon pathway in dorsal root ganglion and displays an analgesic effect (Sun et al, 2022 ). In the light of this, researchers have reviewed that IFN-α and IFN-β may rapidly suppress neuronal activity and synaptic transmission to potent analgesia via nongenomic regulation (Tan et al, 2021 ), while the discrepancy in antinociceptive against pronociceptive effects of type 1 interferons may ascribe to various conditions, and the exact role of STING/type 1 interferons in chronic pain requires further investigation.…”
Section: The Main Downstream Signaling Pathways Of Cgas-sting In Chro...mentioning
confidence: 99%
“…Agonists and inhibitors targeting cGAS-STING have been developed with potentials for the treatment of auto-inflammation, virus infection, and cancers (Ding et al, 2020 ). In chronic-refractory pain, STING-related adjuvant therapy appears to have translational potential, and the latest research has reported that a small molecule drug 7-BIA could alleviate neuropathic pain by upregulating STING and IFN-α in the DRG (Sun et al, 2022 ). There is a possibility of developing new drugs that target the STING signal pathway to treat refractory cancer-induced bone pain or neuropathic pain in patients to avoid systemic effects.…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 99%
“…In a rat model, deficiency of the STING–IFN-I pathway increased the excitability of nociceptors ( Donnelly et al, 2021 ). In the chronic constriction injury model of rats, knockdown of the D-type protein tyrosine phosphatase receptor increased the expression of STING and IFN-α, which attenuated pain ( Sun et al, 2022 ). STING agonists can relieve neuropathic pain in peripheral neuropathy induced by paclitaxel chemotherapy ( Donnelly et al, 2021 ) and pain induced by nerve injury ( Donnelly et al, 2021 ).…”
Section: Effects Of Sting–ifn-i Pathway On Nociceptionmentioning
confidence: 99%
“…Moreover, STING agonists can attenuate fracture-induced pain in tumor-free mice ( Wang et al, 2021 ). Notably, after injecting STING agonists in rats, IFN-I levels in serum, DRG tissues, and bone marrow lysates were significantly upregulated 1000-fold in 4 h and maintained for up to 24 h ( Donnelly et al, 2021 ; Wang et al, 2021 ; Sun et al, 2022 ). Therefore, the STING–IFN-I pathway may promote short-term antinociception.…”
Section: Effects Of Sting–ifn-i Pathway On Nociceptionmentioning
confidence: 99%
See 1 more Smart Citation